Evaluation of ASTER Data Use in Land Use Study in the Mekong delta - Pham, Van Cu (VNU, 2014)
The Mekong Delta in the south of Vietnam is a highly dynamic landscape with rapid changes in land use. Costal forests of mangrove (Rhizophoraceae, onneratiaceae and Avicenniaceae) and the more inland Melaleuca forests are changed into shrimp ponds and rice fields. The complex crop calendar and the diversification of land use types strongly influenced by the agriculture product market createa very complicated land use practice in the Mekong Delta. This increases costal erosion andgives a local rise in temperature. Human activities also increase the risk of forest fires, and corridors are therefore made to protect the remaining forests. Monitoring these changes accurately with a low cost is essential. Existing maps are inaccurate and not updated. ASTER data have a high spatial and radiometric resolution and can be acquired at alow cost. We seek a methodology to optimize differentiation between rice, grassland and forest, forest types, soil types and rice growth stages. Characteristics of each band, band combinations and band ratios are examined. Thermal channels are also used in these combinations to monitor human activities.